Inflammation and oxidative stress in salt sensitive hypertension; The role of the NLRP3 inflammasome - Ertuglu, Lale A.; Mutchler, Ashley Pitzer; Yu, Justin; Kirabo, Annet (Frontiers in Physiology, 2022)
Salt-sensitivity of blood pressure is an independent risk factor for cardiovascular disease and affects approximately half of the hypertensive population. While the precise mechanisms of salt-sensitivity remain unclear, recent findings on body sodium homeostasis and salt-induced immune cell activation provide new insights into the relationship between high salt intake, inflammation, and hypertension. The immune system, specifically antigen-presenting cells (APCs) and T cells, are directly implicated in salt-induced renal and vascular injury and hypertension. Emerging evidence suggests that oxidative stress and activation of the NLRP3 inflammasome drive high sodium-mediated activation of APCs and T cells and contribute to the development of renal and vascular inflammation and hypertension. In this review, we summarize the recent insights into our understanding of the mechanisms of salt-sensitive hypertension and discuss the role of inflammasome activation as a potential therapeutic target.